Partisipasi Petani Terhadap Program Ketahanan Pangan Di Subak Pulagan, Desa Tampaksiring, Kecamatan Tampaksriring, Kabupaten Gianyar - Yustina Sidim; Ni Gst. Ag. Gde Eka Martiningsih; Dian Tariningsih (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2021)
This research is about farmer participation in food security program in Subak Pulagan, Tampaksiring Village, Tampaksiring District, Gianyar Regency. This study aims to find out how farmers participate in food security programs, what factors influence farmer participation in food security programs in Subak Pulagan, Tampaksiring Village, Tampaksiring District, Gianyar Regency. Determination of respondents in this study using a simple random sampling method (randomly) with the number of respondents 35 people, this study uses the methods: (1) Likert scale Farmer participation in food security programs., (2) using multiple linear regression method to determine the factors - What factors influence the participation of farmers in the food security program in Subak Pulagan, Tampaksiring Village, Tampaksiring District, Gianyar Regency. The results showed that the participation of farmers in the planning, implementation and utilization of food security programs in Pulagan subak was high, while their participation in the evaluation was still in the medium category. Overall, farmers' participation in the food security program in Pulagan subak is high, with an average score of 3.89% on average. Farmers' age and formal education have no significant effect on their participation in food security programs. The number of family members and the area of ​​land cultivated by farmers have a very real influence on their participation in food security programs. The higher the number of family members and the area of ​​land cultivated by farmers, the higher the participation in food security programs